Empowering families through social tourism - Kosar, Tahira (2024)
The family holiday characterises the essence of what it means to be a family in contemporary Western society. It exudes family togetherness, strong family bonds, happy memories, and an opportunity to escape from the drudgery of ordinary life (Gram, 2005; Schänzel et al., 2012). Yet, this is by no means the case for every family, and in this research project, I investigate the impact of a short break on families that do not normally go away. Although family tourism has become the norm it remains at the periphery of tourism research (Obrador-Pons, 2011). Receiving even less attention is social tourism which refers to the practice of providing travel opportunities for people who are normally excluded for various reasons including social, economic, cultural or physical (McCabe, 2009; McCabe and Diekmann, 2015). In the UK, charities such as the Family Holiday Association provide short breaks to low-income families (Hunter-Jones, 2011). Often, these families are living in challenging situations such as caring duties or feeling isolated. Consequently, social tourism aims to provide families with the same opportunities to travel and explore new places as other families have (McCabe, 2009). Social tourism has shown to have many benefits, research shows benefits to subjective wellbeing (McCabe and Johnson, 2013), increasing social and family capital (Minnaert et al., 2009), improving older people’s wellbeing (Morgan et al., 2015; Ferrer et al., 2016) and also playing a part in respite care services (Hunter-Jones et al., 2020). However, although there is a growing body of research into social tourism, there is little known on the familial processes that take place whilst on holiday and how they influence family efficacy and family functioning. In addressing this gap this study brings together a critical social psychological framework with a critical realist methodology. Through this approach I present social tourism as a family centric intervention that can empower families. This thesis reports findings from a collaborative qualitative multi-level study where participants consisted of families who had shared in a Family Holiday Association (now known as Family Holiday Charity) short break. Data collection was obtained from semi-structured interviews (n=26). Interview data were analysed using thematic analysis through a critical realist analytic lens. Results suggest that the holiday provides families with the opportunity to participate in normative family activities, that not only reaffirms family identity but gives families a sense of purpose that, in turn, can help families become more future-orientated. The findings of the study indicate social tourism can act as a powerful holistic family intervention and that it can instigate changes in family members facilitating efficacy beliefs and capability. However, through a critical realist understanding it is recognised that any benefits from such interventions are capped by wider structural inequalities that continue to persist.